Optimization of Candida tropicalis growth conditions on silicone elastomer material by response surface methodology - Yogendraiah, Kavyasree Marabanahalli; Sadanandan, Bindu; Kyathsandra Natraj, Lokesh; Vijayalakshmi, Vaniyamparambath; Shetty, Kalidas (Frontiers in Bioengineering and Biotechnology, 2025)
Biofilm in the emerging pathogen Candida tropicalis and the most prevalent Non-Albicans Candida infections is linked to fouling of medical devices and virulence. The growth conditions (temperature, media pH, incubation time, inoculum size, and shaker speed) for clinical cultures of C. tropicalis were optimized on silicone elastomer material by Central composite design based on Response surface methodology. Six clinical cultures (C4, U873, U951, U1179, U1309 and U1360) and a standard culture (MTCC-184) were chosen for the study. Growth and biofilm were quantified for all the cultures by crystal violet (biofilm), MTT (cell viability), calcofluor white (cell mass), and wet and dry weight (cell mass) measurements. Among the isolates, U951 was found to fit the CCD model. The non-normal distribution and heteroscedasticity of the data favored the transformation via CCD-integrated Johnson model profiler for the prediction of the optimal growth conditions. For U951 isolate, biofilm formation was impacted by temperature and incubation time. A direct correlation was observed between biofilm formation and cell viability, with variations in the cell mass in all the cultures. This is the first of its kind study to advance an in vitro silicone elastomer-based high-throughput growth model of C. tropicalis for various applications, including the screening of potential therapeutics.